Impact of Cotton IPM Demonstration - Narula, A.M.; Shashikumar, S.; Chougala, D.G. (Indian Journal of Extension Education, 2022)
Cotton (Gossypium sp.), commonly referred to as â€œwhite goldâ€ is the major commercial crop grown in India , besides fiber cotton ,seed also plays a vital role in the economics of agro industrial development. Karnataka was one of the important cotton areas in India & covered an area of 6.05 lakh ha in 1998- 99. This area in the state decreased over the years. The reasons for decrease in area were due to severe pest problem, price fluctuation and drought. Among these, pest problem made the farmers to spend more on plant protection and also yield level decreased to 201 kg lint/ha in 2005-06 from 244 kg lint/ha in 1998 â€“ 99. Similar decrease in trend was observed in acreage and yield in Belguam district of Karnataka state. The reason for this decrease was severe pest problem, ineffectiveness of chemical insecticides and sole dependence on chemical insecticides.